ANALISIS PENDAPATAN USAHATANI JAGUNG MANIS PADA KELOMPOK TANI SUKAMAJU I DI DESA BULUPONTU JAYA KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Made Antara, Sadam, (AGROTEKBIS, 2016)
The high amount of sweet corn production in the village of Jaya Bulupountu does not guarantee the high income of the farmers, it is caused by other than the production input costs are high it is due to the price received by farmers maize is lower too than the price paid by consumers. The study aims know the amount of income earned by sweet corn farmer in the Jaya village sub district Bulupountu Biromaru Sigi. This study was conducted in the Bulupountu Jaya village Sigi Biromaru sub district in September until November, 2015. The determinant of respondent is done by simple random sampling method by taking as many as 30 respondents sweet corn growers from 90 families. Analysis of the data used is the analysis of income (p = TR - TC) and the results showed that the income of sweet corn farmer in the Bulupountu Jaya village Biromaru Sigi sub district was Rp. 10962.812/0.45 ha/MT or Rp. 243618.0/ha/planting season, with a total cost of Rp. 1.503.371.87/0.45 ha/MT or Rp. 334.159.71/ha/planting season. Sweet corn farming on farmers groups Sukamaju I in the Bulupountu Jaya village Biromaru Sigi sub district.